Strategi Pemasaran untuk Meningkatkan Jumlah Pendaftar di Tadika: Studi Kasus di Tadika Al Fikh Orchard Bandar Parklands Malaysia - Ade Ermanisa; Syahrul Amsari (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the marketing strategies applied by Tadika Al Fikh Orchard Bandar Parklands in increasing the number of student enrollments. This research uses a qualitative approach with a descriptive method to describe the situation and conditions in the field in detail. Data were obtained through interviews, observation, and documentation. The results showed that Tadika Al Fikh Orchard has implemented a fairly appropriate market segmentation by targeting parents who want Islamic-based education and a child-friendly approach. However, there are challenges in terms of a less strategic location, which has led to a decrease in the number of student enrollments in recent years. In addition, promotion through social media and word of mouth proved effective, although direct promotion in the neighborhood still needs to be improved. Based on these findings, some suggestions are to expand market segmentation, increase aggressive promotion, consider opening branches in more strategic locations, and strengthen the advantages of the Islamic and Montessori-based curriculum. This research is expected to provide insights for Tadika Al Fikh Orchard to increase learner enrollment and strengthen its position in the early childhood education market.